2014
DOI: 10.2169/internalmedicine.53.1783
|View full text |Cite
|
Sign up to set email alerts
|

Non-superiority of Kakkonto, a Japanese Herbal Medicine, to a Representative Multiple Cold Medicine with Respect to Anti-aggravation Effects on the Common Cold: A Randomized Controlled Trial

Abstract: Objective Kakkonto, a Japanese herbal medicine, is frequently used to treat the common cold not only with a physician's prescription, but also in self-medication situations. This study aimed to examine whether Kakkonto prevents the aggravation of cold symptoms if taken at an early stage of illness compared with a well-selected Western-style multiple cold medicine. Methods This study was a multicenter, active drug-controlled, randomized trial. Adults 18 to 65 years of age who felt a touch of cold symptoms and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In addition, Okabayashi et al (2014) reported on the effects of kakkonto on the common cold. An RCT comparing kakkonto with multiple Western-style cold medicines demonstrated no difference in the ability to alleviate common cold symptoms, including coldness, nasal, throat, or bronchial symptoms.…”
Section: Common Coldmentioning
confidence: 99%
“…In addition, Okabayashi et al (2014) reported on the effects of kakkonto on the common cold. An RCT comparing kakkonto with multiple Western-style cold medicines demonstrated no difference in the ability to alleviate common cold symptoms, including coldness, nasal, throat, or bronchial symptoms.…”
Section: Common Coldmentioning
confidence: 99%
“…SST is a widely used herbal medicine in various Asian countries including China, Japan, and Korea. [ 10 , 11 ] SST consists of 7 herbal ingredients: Bupleurum falcatum Linne (12 g), Scutellaria baicalensis Georgi (8 g), Panax ginseng C. A. Mey (4 g), Pinellia ternata Breitenbach (4 g), Glycyrrhiza uralensis Fisch. or Glycyrrhiza glabra L. (2 g), Zingiber officinale Roscoe (3 g), and Zizyphus jujuba Miller var.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan several Kampo prescriptions like Maoto, Kakkonto (Kurokawa et al 1996;Okabayashi et al 2014), Shahakusan (Hokari et al 2012), Shoseiryuto Yamada 1994, 1998;Nagai et al 1996;Yamada and Nagai 1998), Daiokanzoto (Watanabe 2018) and Hochuekkito (Dan et al 2018) (Table 1) have been investigated for their effect against influenza virus infection.…”
Section: Anti-viral Activity Of Kampo Prescriptions Such As Maotomentioning
confidence: 99%